Exploring the Use and Cultural Significance of Bimanese Idioms in Social Interactions: Case Study at LDK AL Muhajirin at STKIP Taman Siswa Bima - Ramli; Irma, Ade (Jurnal Genesis Indonesia, 2024)
This research investigates the use and types of Bimanese idioms within the social interactions of LDK AL Muhajirin at STKIP Taman Siswa Bima. Employing a descriptive qualitative methodology, the study examines four recorded interactions and 3 study sessions, revealing 26 instances where Bimanese idioms were utilized. These idiomatic expressions were associated with various pragmatic speech acts, including illocutionary, elocutionary, and perlocutionary acts, involving 17 speakers and 41 listeners. Furthermore, the research categorizes these idioms into distinct types, emphasizing their cultural significance. "Kalemboade" or "lemboade" emerged as the most frequently used idiom, followed by "maja" and "dahu," indicative of broader Bima cultural values, often referred to as "dou mbojo motto." However, the study also highlights the dwindling awareness of certain idioms, such as " ncewi mbei adem," among younger generations. These findings provide valuable insights into the role of Bimanese expressions in social discourse, shedding light on their cultural relevance and evolving use among different age groups. This research contributes to understanding linguistic dynamics within specific cultural contexts and underscores the importance of preserving linguistic heritage in an ever-changing linguistic landscape.